Childhood Maltreatment, Stressful Life Events, Cognitive Emotion Regulation Strategies, and Non-suicidal Self-Injury in Adolescents and Young Adults With First-Episode Depressive Disorder: Direct and Indirect Pathways - Qian, Hong; Shu, Chang; Feng, Li; Xiang, Junyi; Guo, Ying; Wang, Gaohua (Frontiers in Psychiatry, 2022)
Introduction Childhood maltreatment (CM), stressful life events (SLE), and cognitive emotion regulation strategies (CERS) have been considered crucial in the development of non-suicidal self-injury (NSSI) and major depressive disorder (MDD), but the pathways of this association are not clear. We aim to identify direct effects of CM and SLE on NSSI and depression severity and its indirect effects via CERS in adolescents and young adults with a diagnosis of MDD. Methods A total of 114 patients (aged 14–24 years) with first episode MDD were included and further divided into the NSSI group (n = 56) and non-NSSI group (n = 58) according to the DSM-5 criteria. Diagnostic interviews and self-report measures were conducted to assess CM, SLE, CERS, and diagnose NSSI. Severity of depressive symptoms was measured using the Hamilton Rating Scale (HAMD). The structural equation model was used to assess the pathways. Results MDD patients with NSSI had more frequent family history of mental illness, more experience of CM and SLE, more serious depression, less use of adaptive CERS, and more use of maladaptive CERS. In the final structural equation model (χ2 = 4.82, df = 6, p = 0.57, CFI = 1.0, TLI = 1.10, and RMSEA = 0), the experience of CM and SLE showed a significant indirect effect on NSSI through adaptive CERS. CM and SLE only had direct effects on depression severity. Conclusions NSSI are prevalent in adolescents and young adults with MDD and highly intertwined with CM, SLE, and CERS. Adaptive CERS, not maladaptive CERS may be a possible mechanism relating CM and SLE to NSSI in MDD patients.